Associations of eating behaviours, fast food purchasing and availability with BMI-for-age z-score among adolescents in Labuan, Malaysia - Ho, Shu Fen; Chin, Yit Siew; Mohamed Shariff, Abdul Rashid; Lim, Poh Ying (Persatuan Pemakanan Malaysia, 2021)
Introduction: A cross-sectional study was conducted to determine the associations of socio-demographic factors, eating behaviours, fast food purchasing by parents for family meals, and availability of neighbourhood fast-food outlets with BMI-for-age z-score (BAZ) among adolescents. Methods: Through multi-stage stratified cluster sampling method, a total of 420 adolescents from five selected public secondary schools participated in the current study. Data on socio-demographic factors, eating behaviours, and parent’s purchases of fast food were obtained through selfadministered questionnaires. The availability of fast-food outlets was assessed using Geographic Information System (GIS). Body weight and height of the adolescents were measured. Results: The prevalence of overweight, obesity, thinness and severe thinness among adolescents in the present study were 17.6%, 15.5%, 3.1% and 0.7%, respectively. The current findings showed that a higher monthly household income (rs=0.12, p=0.02) and less purchases of fast food by parents for family meals (rs=-0.11, p=0.03) were significantly associated with higher BAZ of the adolescents. However, there were no significant associations between eating outside of home, eating at fast-food restaurants, buying delivery fast food, and availability of neighbourhood fast-food outlets with BAZ. Multiple linear regression showed that less purchases of fast food by parents for family meals significantly contributed towards higher BAZ (β=−0.25, p=0.02). Conclusion: A higher household income and less fast food purchasing by parents were associated with higher BAZ. Fast food purchasing of adolescents were not associated with BAZ. Therefore, an appropriate obesity intervention programme should focus on adolescents and their parents from middle- and high-income households in Labuan.